Cost-Effectiveness of Neoadjuvant Pembrolizumab Plus Chemotherapy Followed by Adjuvant Single-Agent Pembrolizumab for High-Risk Early-Stage Triple-Negative Breast Cancer in the United States - Huang, Min; Fasching, Peter; Haiderali, Amin; Xue, Weiguang; Yang, Chelsey; Pan, Wilbur; Zhou, Zheng Yi; Hu, Peter; Chaudhuri, Mitashri; Le Bailly De Tilleghem, Celine; Cappoen, Nicolas; O’Shaughnessy, Joyce (Advances in Therapy, 2023)
Introduction: The randomized phase III KEYNOTE-522 trial demonstrated that addition of pembrolizumab to neoadjuvant chemotherapy provided a significant improvement in event-free survival and a favorable trend in overall survival for high-risk early-stage triple-negative breast cancer (eTNBC). This analysis evaluated the cost-effectiveness of pembrolizumab in combination with chemotherapy as neoadjuvant treatment and continued as a single-agent adjuvant treatment after surgery vs. neoadjuvant chemotherapy for patients with high-risk eTNBC in the USA. Methods: The analysis was conducted from a US third-party public healthcare payer perspective. A multistate transition model was developed using efficacy and safety data from the KEYNOTE-522 trial. The model included four mutually exclusive health states: event-free, locoregional recurrence, distant metastasis, and death to simulate patients’ lifetime disease course. Quality-adjusted life years (QALYs) were calculated on the basis of EuroQoL-5 Dimensions utility data collected in KEYNOTE-522. Costs for drug acquisition/administration, adverse events, disease management, and subsequent therapies were reported (2021 US dollars). Costs and outcomes were discounted at 3% annually. A series of sensitivity analyses were performed to test the robustness of the main results. Results: In the base case scenario, pembrolizumab plus chemotherapy followed by pembrolizumab resulted in expected gains of 3.37 life years (LYs) and 2.90 QALYs, and an incremental cost of 79,046 versus chemotherapy. The incremental cost per QALY gained was 27,285, which is lower than all commonly cited US willingness-to-pay thresholds. Sensitivity analyses showed the results were robust over plausible values of key model inputs and assumptions. Conclusions: Compared with neoadjuvant chemotherapy, pembrolizumab in combination with chemotherapy as neoadjuvant treatment and continued as a single-agent adjuvant treatment after surgery is considered a cost-effective option for high-risk eTNBC in the USA.
CRIS-Team Scopus Importer:2023-01-27
Keywords: Adjuvant therapy; Cost-effectiveness analysis; Early-stage triple-negative breast cancer; Neoadjuvant therapy; Pembrolizumab